Association between early informed diagnosis and survival time in patients with lung cancer. Issue 5 (7th April 2020) - Su, Tong; He, Chen; Li, Xiaopan; Xiao, Lei; He, Jingwen; Bai, Yonghai; Tang, Yunxiang
Abstract: Objective: As a malignant tumor with high mortality, lung cancer (LC) often causes great trauma to patients, and a series of negative emotions and a heavy psychological burden accompanies poor prognosis. Whether or not to inform the patients of their condition has always been a controversial topic in the medical community. This retrospective cohort study investigated the association between early informed diagnosis and survival time in patients with LC. Methods: A total of 29 825 patients with LC were enrolled between October 2002 and December 2016. The potential factors influencing LC survival were registered, including knowing their cancer diagnosis status, age, gender, pathological type, clinical stage, surgical history, hospital grade, and patient occupation. All participants were followed up every 6 months until June 2017. Results: In June 2017, 23.1% of the participants still survived. Their median survival time (MST) was 11.20 months (95% confidence interval [CI], 10.98‐11.43). Generally, patients that knew their cancer diagnosis had longer MST than those who did not (18.33 months vs 8.77 months, P < .001). By stratified analysis, patients that knew their cancer diagnosis had longer survival time in each subgroup ( P < .001, all subgroups). Cox regression analysis showed that knowing their cancer diagnosis was an independent influencing factor for survival in patients with LC (hazard ratio, 0.826; 95% CI, 0.802‐0.851; P < .001). Conclusions: Knowing their cancer diagnosis contributed to longer survival time in patients with LC, providing clear evidence that medical staff and patients' families should fully disclose cancer diagnoses to patients.